UHPLC-ESI-QE-Orbitrap-MS based metabolomics reveals the antioxidant mechanism of icaritin on mice with cerebral ischemic reperfusion - Yunfeng Tang; Lixin Sun; Yun Zhao; Jingchun Yao; Zhong Feng; Zhong Liu; Guimin Zhang; Chenghong Sun (PeerJ, 2023)
Background Icaritin (ICT) has been previously demonstrated to display protective effects against cerebral ischemic reperfusion (I/R) by inhibiting oxidative stress, but the mechanism remains unclear. This study aimed to explore the mechanism from the perspective of metabolomics. Methods A mice cerebral artery occlusion/reperfusion (MCAO/R) model was explored to mimic cerebral ischemic reperfusion and protective effect of ICT was assessed by neurologic deficit scoring, infarct volume and brain water content. Ultra-high-performance liquid chromatography electrospray ionization orbitrap tandem mass spectrometry (UHPLC-ESI-QE-Orbitrap-MS) based metabolomic was performed to explore potential biomarkers. Brain tissue metabolic profiles were analyzed and metabolic biomarkers were identified through multivariate data analysis. The protein levels of Nrf2, HO-1 and HQO1 were assayed by western blot. The release of malondialdehyde (MDA) and the activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) were detected using corresponding assay kits. Results The results showed that after ICT treatment, the neurological deficit, cerebral infarction area, brain edema and the level of MDA in brain tissue of MCAO/R mice were significantly reduced. Meanwhile, ICT enhanced the activity of SOD, CAT and GSH-Px. Western blot results confirmed that ICT up-regulated the protein levels of antioxidant-related protein including Nrf2, HO-1 and NQO1. According to the metabolomic profiling of brain tissues, clear separations were observed among the Sham, Model and ICT groups. A total of 44 biomarkers were identified, and the identified biomarkers were mainly related to linoleic acid metabolism, arachidonic acid metabolism, alanine, aspartate and glutamate metabolism, arginine biosynthesis, arginine and proline metabolism, D-glutamine and D-glutamate metabolism, taurine and hypotaurine metabolism and purine metabolism, respectively. At the same time, the inhibitory effect of ICT on arachidonic acid and linoleic acid in brain tissue, as well as the promoting effect on taurine, GABA, NAAG, may be the key factors for the anti-neurooxidative function of mice after MCAO/R injury. Conclusion Our results demonstrate that ICT has benefits for MCAO/R injury, which are partially related to the suppression of oxidative stress via stimulating the Nrf2 signaling and regulating the production of arachidonic acid, linoleic acid, taurine, GABA, NAAG in brain tissue.